2013
DOI: 10.18388/abp.2013_1981
|View full text |Cite
|
Sign up to set email alerts
|

The influence of chromone based hydrazones on lipid peroxidation and bFGF concentration in the HL-60 cell line.

Abstract: Natural and synthetic derivatives of benzo-γ-pyrones (i.e. flavones, chromones, and coumarins) and their synthetic analogues possess a wide range of biological properties in vitro and in vivo. In this paper we investigated the influence of two hydrazone compounds of chromones, 3-{[(2-dimethoxytiophosphoryl)-2-methylhydrazono]-methyl}-chromen-4-one (CH-3) and 2-amino-6-chloro-3-[(2-hydroxyethyl)-hydrazonomethyl]-chromen-4-one (A-12), on lipid peroxidation and bFGF concentration in theHL-60 cells. Both of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Previous studies have confirmed the antiproliferative properties [ 12 , 31 ] and biochemical activity [ 32 , 33 ] of 3-formylchromone derivatives. Moreover, biological activity of copper (II) complexes of 3-formylchromone, was also described [ 21 ]; however, hydrazine and hydrazide derivatives of benzopyrones with fluorine substituents remain a poorly-analyzed group of compounds.…”
Section: Introductionmentioning
confidence: 63%
“…Previous studies have confirmed the antiproliferative properties [ 12 , 31 ] and biochemical activity [ 32 , 33 ] of 3-formylchromone derivatives. Moreover, biological activity of copper (II) complexes of 3-formylchromone, was also described [ 21 ]; however, hydrazine and hydrazide derivatives of benzopyrones with fluorine substituents remain a poorly-analyzed group of compounds.…”
Section: Introductionmentioning
confidence: 63%